Retraction notice to “Toxicity of spike fragments SARS-CoV-2 S protein for zebrafish: A tool to study its hazardous for human health?” [Sci. Total Environ. 813 (2022) / 152345] - Bianca H. Ventura Fernandes; Natália Martins Feitosa; Ana Paula Barbosa; Camila Gasque Bomfim; Anali M.B. Garnique; Ivana F. Rosa; Maira S. Rodrigues; Lucas B. Doretto; Daniel F. Costa; Bruno Camargo-dos-Santos; Gabrielli A. Franco; João Favero Neto; et al. (Science of The Total Environment, 2024)

Development of an analytical platform for the affinity screening of natural extracts by SEC-MS towards PPARα and PPARγ receptors - G. De Soricellis; F. Rinaldi; S. Tengattini; C. Temporini; S. Negri; D. Capelli; R. Montanari; H. Cena; S. Salerno; G. Massolini; F. Guzzo; E. Calleri (Analytica Chimica Acta, 2024)

Species portfolio effects dominate seasonal zooplankton stabilization within a large temperate lake - Reilly F. O'Connor; Bailey C. McMeans; Neil Rooney; Matthew M. Guzzo; Joelle D. Young; Kevin S. McCann (Ecology, 2023)
Portfolio effects (PEs) in ecology refer to the suite of phenomenon where the temporal variation of aggregate ecosystem properties (i.e., abundance) is lower than that of their ecosystem components. An example of this is where differential responses of species to environmental variation generate stability at higher levels of ecological organization (e.g., local community, metapopulation, metacommunity). Most of the research examining such PEs has focused on spatial or interannual variation of ecosystems; however, as global change continues to alter seasonality and ecosystem functioning, understanding the underlying food web structures that help maintain stability at multiple spatial and temporal scales is critical to managing ecological systems. Recent advances investigating diversity‐stability relationships has led to the development of frameworks that incorporate a metacommunity perspective which allows for the partitioning of PEs across organizational scales (i.e., local community, metapopulation, cross‐community, metacommunity) from local population dynamics (total). This partitioning yields insights into the mechanisms that generate observed PEs in nature. Here, we employed one of these recently developed frameworks on a temporally (1986–1999, 2008–2019) and spatially (five sampling stations, local communities) extensive data set of zooplankton abundance (e.g., density) within a large temperate lake to investigate how temporal (seasonal) and spatial (among site) PEs influence stability within the zooplankton metacommunity. We found that seasonal asynchrony of different zooplankton species within local communities and across communities generated the vast majority of stabilization, while spatial (i.e., metapopulation) dynamics were more synchronous and contributed little to overall system stability. Furthermore, significantly positive diversity‐asynchrony relationships at the total, local‐ and cross‐community scales were found as asynchrony was positively correlated with local Shannon diversity. Last, a comparison of PEs over the time periods, during which significant local and global changes (i.e., climate warming, invasive species) have occurred suggests that PEs may be eroding, as increasingly synchronous dynamics and declining diversity in recent years have led to a rise in metacommunity variability. We end by arguing for the critical importance of understanding seasonally driven stabilizing mechanisms as local and global changes threaten to fundamentally alter seasonal signals with potentially strong implications for the structures that lend stability to ecosystems.

Adult attractiveness and oviposition preference of Zabrotes subfasciatus toward genotypes of common bean Phaseolus vulgaris - Elio C. Guzzo; José D. Vendramim; André L. Lourenção; Alisson F. Chiorato; Sérgio A. M. Carbonell; Osvaldo M. B. Corrêa (Phytoparasitica, 2018)

No Correlation of Morpho-Agronomic Traits of Phaseolus vulgaris (Fabaceae) Genotypes and Resistance to Acanthoscelides obtectus (Say) and Zabrotes subfasciatus (Boheman) (Coleoptera: Chrysomelidae) - E C Guzzo; J D Vendramim; A F Chiorato; A L Lourenção; S A M Carbonell; O M B Corrêa (Neotropical Entomology, 2015)

Flow cytometry and sorting of protoplasts from carrot cell cultures reveal two cell subpopulations with different morphogenetic potential - Guzzo F.; Cantamessa K.; Portaluppi P.; Levi M. (Plant Cell Reports, 2002)

Outbreak of African Tick-Bite Fever in Six Italian Tourists Returning from South Africa - G. Caruso; C. Zasio; F. Guzzo; C. Granata; V. Mondardini; E. Guerra; E. Macrì; P. Benedetti (European Journal of Clinical Microbiology & Infectious Diseases, 2002)